Pratiche politiche, scritture documentarie e costruzione identitaria della comunità cittadina. L’esempio di Firenze in età comunale (secoli XII-XIV) - Gualtieri, Piero; Zorzi, Andrea (Scrineum, 2013)
Particularly reffering to the digital work named Atlante della documentazione comunale, the research centered on the series of council decisions books, the only ones (among those produced before 1343) that survived until nowadays in a continuous form, and was focused upon legislation regarding Florentine magnates. This matter turned out to be an excellent perspective allowing to reconstruct the communal normative system, that in Florence got a crucial qualitative leap in the development of all its political and cultural potentialities at the time when new “popolo” government took the power, in 1280's.